High-power lithium ion power battery

Through the design of stacked composite electrode structure and conductive rubber matrix, the problem of insufficient energy density and power output in the field of electric aircraft is solved, and a battery system with high energy density and high power performance is realized, meeting the efficient power supply needs of electric aircraft.

CN119674264APending Publication Date: 2025-03-21ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411538405.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have low energy density, insufficient power output and self-discharge problems in electric aircraft and other fields, making it difficult to meet the needs of efficient power systems.

Method used

The stacked composite positive electrode sheet, lithium titanate negative electrode sheet and carbon-based composite electrode sheet are used to design a lightweight battery structure to achieve efficient combination of supercapacitors and lithium-ion batteries.

Benefits of technology

It significantly improves the energy density and power performance of the system, extends the cycle life of the battery, and can continuously output high power pulses, meeting the high energy and high power needs of electric aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674264A_ABST
    Figure CN119674264A_ABST
Patent Text Reader

Abstract

The invention discloses a high-power lithium ion power battery which comprises a composite positive pole piece, a lithium titanate negative pole piece and a carbon-based composite electrode piece which are stacked, polymer solid electrolytes are arranged between the composite positive pole piece and the lithium titanate negative pole piece, and polymer solid electrolytes are arranged between the lithium titanate negative pole piece and the carbon-based composite electrode piece; at least one of the composite positive electrode plate, the lithium titanate negative electrode plate and the carbon-based composite electrode plate adopts a conductive rubber matrix as a current collector, and the conductive rubber matrix comprises polydimethylsiloxane (PDMS), a conductive material and mesocrystal anatase titanium dioxide. The performance of the supercapacitor and the lithium ion battery is improved through the novel material, meanwhile, the battery structure is subjected to lightweight design, efficient combination of the supercapacitor and the lithium ion battery is achieved, and the energy density and the power performance of the system are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a high-power lithium ion power battery, which significantly improves the power performance and cycle life of the lithium ion battery. Background Art

[0002] The emerging all-electric urban air mobility (UAM) market can reduce carbon emissions in urban environments and avoid problems caused by road traffic congestion. With the advancement of technology, lithium-ion battery technology has become the only power source in the field of electric aviation. In terms of long-range flight, the high energy density of lithium-ion batteries can significantly extend the endurance of electric aircraft. The higher power performance and lower self-discharge rate of lithium-ion batteries enable drones to perform tasks more efficiently and extend mission time. Compared with automotive lithium-ion power batteries, lithium-ion power batteries for electric aviation need further improvement in energy density and power performance. However, energy density and power performance are the "seesaw" of lithium-ion battery performance, and there is a relationship of one rising and the other falling. The combination of lithium-ion batteries and supercapacitors can achieve the improvement of energy density and power performance at the same time. Compared with lithium-ion batteries, it has higher power performance and higher energy density than supercapacitors.

[0003] For example, the patent with application number CN202111338571.2 proposes a "bipolar capacitor auxiliary battery", which connects a lithium-ion battery in parallel to a bipolar capacitor composed of a first and a second capacitor connected in series. The bipolar capacitor in this scheme has low energy utilization due to its series structure, and the overall energy density of the system is low. In addition, the structure is complex, the manufacturing cost is high, and the applicable scenarios are limited.

[0004] Another example is the patent with application number CN202211511822.7, which proposes "electric aircraft composite energy system optimization configuration method, system and storage medium". This solution uses the optimization design model to optimally configure the hydrogen storage system, fuel cell, lithium-ion battery and supercapacitor by inputting the technical parameters of the composite energy system and the energy requirements of the electric aircraft. Although this method can achieve the optimal configuration of different energy devices in the electric aircraft system, it mainly focuses on the allocation of system parameters and ignores the optimization of the energy equipment itself, especially in terms of improving energy density and power density. No effective solution has been proposed, making it difficult to be widely used in fields with high energy density requirements.

[0005] In summary, although the existing technical solutions have proposed a design idea of ​​combining lithium-ion batteries with supercapacitors to improve system performance, they generally have defects such as low energy density, insufficient power output, and difficulty in effectively solving the self-discharge problem. Therefore, it is urgent to develop a high-power lithium-ion power battery with a composite power system to overcome the shortcomings of the existing technology, further improve the energy density and power density, and meet the needs of electric aircraft, electric vehicles and other fields for efficient power systems. Summary of the invention

[0006] The purpose of the present invention is to provide a high-power lithium-ion power battery and a preparation method thereof, to improve the performance of supercapacitors and lithium-ion batteries through new materials, and to perform a lightweight design on the battery structure, so as to achieve efficient combined use of supercapacitors and lithium-ion batteries, significantly improve the energy density and power performance of the system, and provide a technical reference for the design of lithium-ion power batteries for low-altitude aircraft.

[0007] The technical solution adopted by the present invention to solve the above technical problems is:

[0008] A high-power lithium-ion power battery, comprising a stacked composite positive electrode sheet, a lithium titanate negative electrode sheet and a carbon-based composite electrode sheet, wherein a polymer solid electrolyte is provided between the composite positive electrode sheet and the lithium titanate negative electrode sheet, and between the lithium titanate negative electrode sheet and the carbon-based composite electrode sheet;

[0009] At least one of the composite positive electrode plate, the lithium titanate negative electrode plate and the carbon-based composite electrode plate uses a conductive rubber matrix as a current collector, and the conductive rubber matrix includes polydimethylsiloxane (PDMS), a conductive material and mesogenic anatase titanium dioxide.

[0010] The stacked composite electrode structure can effectively improve the energy density and power density, achieve higher battery performance, and meet the high energy and high power requirements of electric aircraft.

[0011] Preferably, the stacked composite positive electrode sheet and lithium titanate negative electrode sheet are used as a first stacking unit, and the stacked composite positive electrode sheet, lithium titanate negative electrode sheet and carbon-based composite electrode sheet are used as a second stacking unit, and a plurality of the first stacking units are stacked alternately and then stacked with the second stacking unit, or only a plurality of the second stacking units are stacked alternately, or a plurality of the second stacking units are stacked and then stacked with the first stacking unit;

[0012] A polymer solid electrolyte is provided between two adjacent first lamination units, between two adjacent second lamination units, and between the first lamination unit and the second lamination unit.

[0013] By designing the alternating stacking of the first and second laminate units, the energy conversion efficiency and current conduction capacity of the battery are improved, and the space utilization of the battery is optimized. The polymer solid electrolyte between adjacent units also enhances the interface contact and improves the cycle performance and stability of the battery.

[0014] Preferably, two outer side surfaces of the lithium-ion power battery are provided with polymer solid electrolytes, and the thickness of the polymer solid electrolyte is 5 μm-20 μm.

[0015] Placing a polymer solid electrolyte on the outside of the battery helps improve the mechanical strength and safety of the overall structure while ensuring the stability of the battery under extreme conditions. Controlling the thickness between 5μm-20μm can reduce material costs while maintaining performance.

[0016] Preferably, the mass ratio of polydimethylsiloxane PDMS, conductive material and mesogenic anatase titanium dioxide powder in the conductive rubber matrix is ​​5-9: 0.05-0.25: 0.15-0.45.

[0017] The optimized ratio of the conductive rubber matrix can effectively improve the conductivity and durability of the electrode, enhance the charging and discharging efficiency of the battery, and extend the battery life. This combination unexpectedly improves the performance of the battery in high temperature and high humidity environments.

[0018] Preferably, the conductive material includes at least one of single-walled carbon nanotubes (SWCNTS), mesoporous carbon, graphene, carbon black, conductive graphite, Ketjen black, covalent organic frameworks (COFs), and metal organic frameworks (MOFs).

[0019] The combination of various conductive materials with polydimethylsiloxane (PDMS) and mesogenic anatase titanium dioxide powder not only improves the conductivity, but also reduces costs through diversity and increases the market competitiveness of batteries. This combination has a unique composite effect and improves the overall performance of the battery.

[0020] Preferably, the carbon-based composite electrode plate comprises a conductive agent, a dispersant, a first binder and mesogenic anatase titanium dioxide in a mass ratio of 81-93:0.5-1.5:1.5-4.0:2.0-4.5.

[0021] Preferably, the conductive agent includes at least one of graphene GN, conductive carbon black, conductive graphite, carbon nanotubes, and Ketjen black.

[0022] Preferably, the composite positive electrode plate comprises positive electrode material, sulfide solid electrolyte, mesogenic anatase titanium dioxide, lithium salt and positive electrode binder in a molar ratio of 30-50:3-8:1.5-5.0:0.5-2.5:0.5-1.5.

[0023] Preferably, the thickness of the conductive rubber substrate is 3 μm-30 μm.

[0024] Preferably, the mesocrystalline anatase titanium dioxide powder is prepared by: dissolving a titanium source in a 1mol / L-3mol / L hydrochloric acid solution, the volume ratio of the titanium source to the hydrochloric acid solution being 1-3:4-10, stirring at 40°C-100°C for 40h-60h, centrifuging to obtain a white product, washing the white product with deionized water to remove residual non-polar ions, and then vacuum drying the white product at 80°C-120°C for 12h-36h, and finally calcining at 400°C-500°C in air for 12h-24h to obtain the mesocrystalline anatase titanium dioxide powder. .

[0025] Compared with the prior art, the advantages of the present invention are:

[0026] 1. In the composite power supply system prepared by the present invention, the high-nickel positive electrode and the lithium titanate negative electrode constitute the lithium-ion battery part, which mainly improves the energy density of the system; the lithium titanate pole piece and the graphene pole piece constitute the supercapacitor part, which mainly improves the power density of the system. During the first charging process, the high-nickel positive electrode and the lithium titanate negative electrode are connected to form a conventional lithium-ion battery charging. After the charging is completed, the high-nickel electrode and the graphene electrode are connected for a duration of 10-30S. Due to the potential difference between the two, electrons flow from the graphene electrode to the high-nickel electrode. The surface of the graphene electrode adsorbs anions in the electrolyte and forms a supercapacitor with the lithium titanate negative electrode at this time, which can be discharged at high power. This process is called the self-charging stage of the supercapacitor. When the high-power discharge of the supercapacitor is completed, the lithium-ion battery part can be continuously discharged for a long time with a small current. At this time, the power supply system presents the comprehensive characteristics of a supercapacitor-lithium-ion battery. Repeating the above self-charging and discharging stages can achieve continuous high-power pulse output to meet the high-power requirements of the vertical lift and landing stages of electric aircraft.

[0027] 2. The high-performance lithium-ion power battery prepared is a supercapacitor-lithium-ion battery composite system with multiple power output modes. It can provide instantaneous peak power and stable power output. When discharging continuously under low current, the high-nickel positive electrode and graphene are connected to form the positive electrode, and the lithium titanate pole piece serves as the common negative electrode. The high-nickel electrode inside the system accepts lithium ions and electrons for reduction reaction, and the graphene electrode accepts electrons to provide capacity. The external circuit electrons flow from the lithium titanate negative electrode to the high-nickel electrode and the graphene electrode. When discharging with a large current, the external circuit electrons mainly flow from the lithium titanate negative electrode to the graphene electrode, and the system mainly presents the characteristics of a supercapacitor. Therefore, the discharge rate performance of the composite system is significantly improved, extending the cycle life of the power system when it is quickly discharged. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for use in the specific implementation or the description of the prior art are briefly introduced below.

[0029] Figure 1 This is a schematic diagram of the structure of the lithium-ion power battery prepared in Example 1 of the present invention;

[0030] Figure 2 This is a schematic diagram of the structure of a lithium-ion power battery prepared in Example 5 of the present invention;

[0031] Figure 3 This is a schematic diagram of the structure of the lithium-ion power battery prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0033] A high-power lithium-ion power battery is prepared by the following method:

[0034] Step 1: Preparation of mesocrystalline anatase titanium dioxide powder

[0035] First, a certain amount of titanium source is dripped into 1mol / L-3mol / L hydrochloric acid, wherein the volume ratio of titanium source to hydrochloric acid is 1-3:4-10, and the titanium source used includes but is not limited to dichlorodipentadienyl titanate, tetraisopropoxytitanium, tetrabutyl titanate, titanium citrate, titanium tetrachloride, etc. Then, stirring is continued at 40℃-100℃ for 40-60 hours, and a white product is obtained after centrifugation, and the residual non-polar ions are washed 3-6 times with deionized water. After the white product is vacuum dried at 80℃-120℃ for 12-36 hours, it is further calcined in air at 400℃-500℃ for 12-24 hours to obtain mesocrystalline anatase titanium dioxide powder. Compared with conventional nano- and micron-sized titanium dioxide materials, the synergistic effect of the inherent intergranular rapid diffusion network inside the mesocrystalline anatase titanium dioxide makes its lithium ion diffusion rate higher and can significantly improve the cycle stability of the material. The mesocrystalline anatase titanium dioxide prepared by the present invention includes pure titanium dioxide and its doped and modified derivatives, including nitrogen doping, carbon doping, sulfur doping, various metal and oxide modifications, and the like.

[0036] Step 2: Prepare the conductive rubber substrate

[0037] Polydimethylsiloxane (PDMS, Sylgard184), commercial single-walled carbon nanotubes (SWCNTS, tube diameter 2nm-10nm, tube length 5μm-30μm) and the mesogenic anatase titanium dioxide powder prepared in step 1 are mixed in a mass ratio of 5-9: 0.05-0.25: 0.15-0.45, stirred at room temperature for 30-60 minutes, extruded and cured at room temperature to obtain a conductive rubber matrix with a matrix thickness of 3μm-30μm. In order to optimize the interface contact performance of the conductive rubber matrix, the surface of the prepared conductive rubber matrix is ​​roughened. The present invention adopts a simple sandblasting process, using quartz sand, and spraying clean and dry compressed air of 0.2MPa-0.7MPa onto the surface of the conductive rubber, and the operating environment humidity is kept below -10°C. The present invention uses polydimethylsiloxane PDMS, which is non-toxic and tasteless, has excellent flexibility and physical properties, and can be used as a matrix to prepare flexible lithium-ion power batteries, realize lightweight battery design, and improve energy density. At the same time, it has an electric field shielding effect, which can improve the safety of lithium-ion power systems. Adding single-walled carbon nanotubes and mesogenic anatase titanium dioxide powder can significantly improve the conductivity of conductive rubber, which is beneficial to improving power performance. Single-walled carbon nanotubes can be replaced by one or more other highly conductive materials, including but not limited to mesoporous carbon, graphene, carbon black, conductive graphite, Ketjen black, covalent organic framework structure COFs, metal organic framework MOFs, etc.

[0038] Step 3: Prepare the composite positive electrode sheet

[0039] The high nickel ternary positive electrode material, sulfide solid electrolyte, mesomorphous anatase titanium dioxide, lithium salt and binder are added to dimethyl sulfoxide in a molar ratio of 30-50: 3-8: 1.5-5.0: 0.5-2.5: 0.5-1.5, stirred at room temperature for 12-24 hours and mixed evenly to obtain a positive electrode slurry, and the mass ratio of high nickel ternary material to dimethyl sulfoxide is 11-20: 12-25. The positive electrode slurry is coated on the conductive rubber substrate prepared in the above step 2 at room temperature by a doctor blade method or a transfer coating method to obtain a composite positive electrode with a certain thickness. The lithium salt used is one or more of lithium bis(oxalate borate) LiBOB, lithium hexafluorophosphate LiPF6, lithium bis(fluorosulfonyl imide) LiFSI, and lithium bis(trifluoromethylsulfonyl imide) LITFSI. The binder used is one of polyacrylonitrile PAN, polyimide PI, polyvinyl alcohol PVA, polyvinylidene fluoride PVDF, polyacrylamide PAM, etc. The sulfide solid electrolyte includes but is not limited to binary sulfide electrolytes (such as Li3PS4 and Li7P3S 11 ), ternary sulfide solid electrolytes (such as Li 10 GeP2S 12and Li6PS5X (X = Cl, Br and I)). The dimethyl sulfoxide solvent used can be replaced by one of the polar solvents such as acetonitrile, formamide, trifluoroacetic acid, DMF, hexamethylphosphoramide, methanol, acetic acid, ethanol, isopropanol, pyridine, tetramethylethylenediamine, acetone, triethylamine, n-butanol, dioxane, tetrahydrofuran, methyl formate, etc. The coating thickness of the positive electrode slurry is 150-500 microns. The coated composite positive electrode sheet is rolled under a pressure of 20MPa-50MPa to obtain a dense composite positive electrode, and the rolled positive electrode is punched as required. After punching, the positive electrode sheet is connected to the aluminum pole ear by laser welding, the laser beam is irradiated on the upper aluminum pole ear, and the conductive rubber matrix is ​​closely attached to the upper aluminum pole ear for lap welding.

[0040] Step 4: Preparation of lithium titanate negative electrode

[0041] Lithium titanate, conductive agent, binder and deionized water are put into a ball mill according to a mass ratio of 50-100: 0-50: 1-10: 300-500, the ball-to-material ratio is 1.2-1.7: 0.9-1.1, and the grinding time is 50-80 minutes to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on the conductive rubber substrate prepared in the above step 2 by a scraper method or a transfer coating method, with a coating thickness of 50-300 μm, and then dried, rolled and punched to obtain a lithium titanate negative electrode sheet. After punching, the positive electrode sheet is connected to the nickel-plated copper pole ear or aluminum pole ear by laser welding, the laser beam is irradiated on the upper metal pole ear, and the conductive rubber substrate is closely attached to the upper metal pole ear for lap welding. The negative electrode conductive agent in the present invention includes but is not limited to conductive carbon black, conductive graphite, carbon nanotubes, Ketjen black, graphene and other conductive agents for lithium ion batteries; the negative electrode binder in the present invention includes but is not limited to styrene-butadiene rubber SBR, carboxymethyl cellulose and its derivatives, polyacrylic acid PAA, polyacrylonitrile PAN and other binders for lithium ion battery negative electrodes; the negative electrode slurry process in the present invention includes but is not limited to ball milling, dry mixing, wet slurrying and all other slurry processes applied to lithium ion negative electrodes; the negative electrode coating process in the present invention includes but is not limited to transfer coating, scraper method, extrusion coating, dry electrode and all other lithium ion battery coating processes.

[0042] Step 5: Preparation of carbon-based composite electrode plates

[0043] Graphene GN, dispersant, first binder and mesomorphous anatase titanium dioxide powder are added to N-methylpyrrolidone (NMP) in a mass ratio of 81-93: 0.5-1.5: 1.5-4.0: 2.0-4.5, and ultrasonicated for 30-60 minutes at room temperature to form a uniformly mixed carbon-based slurry, and the carbon-based slurry is evenly coated on the conductive rubber substrate prepared above by a scraper method or a transfer coating method, with a coating thickness of 20-200μm, and then dried, rolled, and punched to obtain a carbon-based composite electrode pole piece. Graphene has excellent electrical conductivity, but due to its one-dimensional structure, the lithium ion transmission channel may be limited. The addition of mesomorphous anatase titanium dioxide powder will provide more lithium ion deintercalation sites, which will help improve the lithium ion transmission speed in the graphene pole piece. After punching, laser welding is used to connect the pole piece to the nickel-plated copper pole ear. The laser beam is irradiated on the upper metal pole ear, and the conductive rubber matrix is ​​closely attached to the upper metal pole ear for lap welding. In addition to graphene, the conductive agent used can also be conductive carbon black, conductive graphite, carbon nanotubes, Ketjen black, etc.; the binder used includes but is not limited to styrene-butadiene rubber SBR, carboxymethyl cellulose and its derivatives, polyacrylic acid PAA, polyacrylonitrile PAN, etc.; the homogenization process used includes but is not limited to ultrasonic mixing, ball milling, dry mixing, wet homogenization, etc.; the coating process used includes but is not limited to transfer coating, scraper method, extrusion coating, dry electrode, etc.

[0044] Step 6: Coat the surface of the composite positive electrode sheet, lithium titanate negative electrode sheet, and carbon-based composite electrode sheet prepared in step 3, step 4, and step 5 with a thin layer of polymer solid electrolyte, the thickness of the polymer solid electrolyte is 5μm-20μm, and the polymer solid electrolyte used includes but is not limited to polyethylene oxide (PEO), polyvinyl alcohol (PEG), polypropylene (PP), polyacrylate (PBA), polycarbonate (PCE), polypropylene (PAN), polytrimethylene carbonate (PTMC), polyvinyl chloride (PVC), polyamide (PA), polyvinylidene fluoride (PVDF), etc. Then stack the coated composite positive electrode sheet, lithium titanate negative electrode sheet, and carbon-based composite electrode sheet in sequence, as shown in the following example. Figure 1As shown, a laminated soft-package composite power system is assembled. In order to ensure a tight interface fit, a certain external pressure (0.1-0.5MPa) is applied during the assembly process. The size and shape of the prepared composite power system are not limited, and it has a certain flexibility, and can be bent and assembled according to actual needs. The dispersants used include polymer dispersants, inorganic dispersants and composite dispersants, wherein the polymer dispersants include but are not limited to one or more of polyvinyl pyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyamide, polyvinyl chloride, polyimide or polycarbonate; the inorganic dispersants include but are not limited to one or more of lithium carbonate, silicon dioxide, zinc oxide, aluminum oxide or boehmite; the composite dispersants include but are not limited to the above-mentioned polymer dispersants or inorganic dispersants connected to the new functional group modified materials, the functional groups include but are not limited to quaternary ammonium, quaternary ammonium salts, halamines, etc.

[0045] Embodiment 1,

[0046] Step 1: Preparation of mesocrystalline anatase titanium dioxide powder

[0047] First, a certain amount of titanium source was dripped into 1.5 mol / L hydrochloric acid, where the volume ratio of titanium source to hydrochloric acid was 1:3, and the titanium source used was tetraisopropoxy titanium. Then, stirring was continued at 70°C for 52 hours, and a white product was obtained after centrifugation. The product was washed with deionized water 5 times to remove the residual non-polar ions. After the white product was vacuum dried at 110°C for 26 hours, it was further calcined at 450°C in air for 20 hours to obtain mesomorphous anatase titanium dioxide powder.

[0048] Step 2: Prepare the conductive rubber substrate

[0049] Polydimethylsiloxane (PDMS, Sylgard184), commercial single-walled carbon nanotubes (SWCNTS, tube diameter 2.5nm, tube length 20μm) and the mesogenic anatase titanium dioxide powder prepared in step 1 are mixed in a mass ratio of 6:0.19:0.3, stirred at room temperature for 45 minutes, extruded and cured at room temperature to obtain a conductive rubber matrix with a thickness of 5μm. The conductive rubber matrix is ​​sandblasted by the present invention, using quartz sand and spraying it onto the surface of the conductive rubber with 0.3MPa clean and dry compressed air, and the operating environment humidity is maintained at -20°C.

[0050] Step 3: Prepare the composite positive electrode sheet

[0051] High nickel ternary positive electrode material, sulfide solid electrolyte, mesogenic anastase titanium dioxide, lithium bis(trifluoromethanesulfonic acid amide) LITFSI and polyvinylidene fluoride PVDF are added to dimethyl sulfoxide in a molar ratio of 32:5:2.1:1.9:1.3, stirred at room temperature for 15 hours to mix evenly to obtain positive electrode slurry, and the mass ratio of high nickel ternary material to dimethyl sulfoxide is 17:20. The positive electrode slurry is applied to the conductive rubber substrate prepared in the above step 2 by transfer coating at room temperature to obtain a composite positive electrode with a certain thickness, and the coating thickness is 220 microns. The coated composite positive electrode sheet is rolled at a pressure of 35MPa to obtain a dense composite positive electrode, and the rolled positive electrode is punched as required. The sulfide solid electrolyte is a ternary sulfide solid electrolyte Li 10 GeP2S 12 After punching, the positive electrode sheet is connected to the aluminum pole ear by laser welding, the laser beam is irradiated on the upper aluminum pole ear, and the conductive rubber matrix is ​​closely attached to the upper aluminum pole ear for lap welding.

[0052] Step 4: Preparation of lithium titanate negative electrode

[0053] Lithium titanate, conductive carbon black, styrene butadiene rubber (SBR) and deionized water were put into a ball mill at a mass ratio of 90:5:5:180, with a ball-to-material ratio of 1.4:1.0, and the grinding time was 65 minutes to obtain a negative electrode slurry. The mixed negative electrode slurry was evenly coated on the conductive rubber substrate prepared in the above step 2 by a scraper method, with a coating thickness of 150 μm. After drying, rolling and punching, a lithium titanate negative electrode sheet was obtained. After punching, the positive electrode sheet was connected to the nickel-plated copper pole ear or aluminum pole ear by laser welding, the laser beam was irradiated on the upper metal pole ear, and the conductive rubber substrate was closely attached to the upper metal pole ear for lap welding.

[0054] Step 5: Preparation of carbon-based composite electrode sheets

[0055] Graphene GN, dispersant, polyacrylic acid PAA and mesogenic anatase titanium dioxide powder were added to N-methylpyrrolidone (NMP) in a mass ratio of 89:1.1:2.7:3.5, and ultrasonicated for 50 minutes at room temperature to form a uniformly mixed carbon-based slurry. The carbon-based slurry was evenly coated on the conductive rubber substrate prepared above by a scraper method with a coating thickness of 90 μm. After drying, rolling and punching, a carbon-based composite electrode pole piece was obtained. After punching, the pole piece was connected to the nickel-plated copper pole ear by laser welding, the laser beam was irradiated on the upper metal pole ear, and the conductive rubber substrate was closely attached to the upper metal pole ear for lap welding.

[0056] Step 6: A thin layer of polymer solid electrolyte is applied to the surface of the composite positive electrode plate, lithium titanate negative electrode plate, and carbon-based composite electrode plate prepared in step 3, step 4, and step 5. The thickness of the polymer solid electrolyte on the surface of the composite positive electrode plate and lithium titanate negative electrode plate is 18 μm, and the polymer solid electrolyte used is polyethylene oxide (PEO). A layer of polymer solid electrolyte is applied to the surface of the carbon-based composite electrode plate, and the thickness of the polymer solid electrolyte is 8 μm, and the polymer solid electrolyte used is polyethylene oxide (PEO).

[0057] Then the coated composite positive electrode sheet, lithium titanate negative electrode sheet and carbon-based composite electrode sheet are stacked in sequence, as shown in the following example. Figure 1 As shown, a laminated soft-package composite power system is assembled. In order to ensure a tight interface fit, a certain external pressure of 0.35 MPa is applied during the assembly process.

[0058] like Figure 1 As shown, the prepared lithium-ion power battery includes a composite positive electrode sheet, a lithium titanate negative electrode sheet and a carbon-based composite electrode sheet stacked in sequence from bottom to top, and a polymer solid electrolyte is provided between the composite positive electrode sheet and the lithium titanate negative electrode sheet, between the lithium titanate negative electrode sheet and the carbon-based composite electrode sheet, and on the two outer sides of the lithium-ion power battery.

[0059] Embodiment 2,

[0060] Compared with Example 1, the preparation method of mesocrystal rutile titanium dioxide in Example 2 is as follows: first, a certain amount of titanium source is dripped into 1 mol / L hydrochloric acid, wherein the volume ratio of titanium source to hydrochloric acid is 3:10, and the titanium source used is tetrabutyl titanate. Then, stirring is continued at 100°C for 40 hours, and a white product is obtained after centrifugation, and the residual non-polar ions are washed 6 times with deionized water. After the white product is vacuum dried at 120°C for 12 hours, it is continued to be calcined in air at 500°C for 24 hours to obtain mesocrystal rutile titanium dioxide powder. The remaining conditions are the same as those in Example 1.

[0061] Embodiment 3,

[0062] Compared with Example 1, the preparation method of the conductive rubber matrix in Example 3 is as follows: polydimethylsiloxane (PDMS, Sylgard 184), commercial single-walled carbon nanotubes (SWCNTS, tube diameter 10nm, tube length 5μm) and the mesogenic anatase titanium dioxide powder prepared in step 1 are mixed in a mass ratio of 5:0.05:0.45, stirred at room temperature for 60 minutes, and extruded and cured at room temperature to obtain a conductive rubber matrix with a thickness of 30μm. Then, a simple sandblasting treatment is adopted, using quartz sand, and spraying clean and dry compressed air of 0.7MPa onto the surface of the conductive rubber, and the operating environment humidity is maintained at -15°C. The remaining conditions are the same as those in Example 1.

[0063] Embodiment 4,

[0064] Compared with Example 1, the preparation method of the lithium titanate negative electrode sheet in Example 4 is: lithium titanate, conductive agent, styrene butadiene rubber SBR and deionized water are put into a ball mill according to a mass ratio of 100:50:1:300, the ball-to-material ratio is 1.5:0.9, the grinding time is 80 minutes, the mixed slurry is evenly coated on the conductive rubber substrate prepared in the above step 2 by a scraper method, the coating thickness is 50 μm, and the negative electrode sheet is obtained after drying, rolling and punching. The other conditions are the same as those in Example 1.

[0065] Embodiment 5,

[0066] Using the preparation method in Example 1, when coating the polymer solid electrolyte in step S6, the two sides of the lithium-ion power battery located on the outside are not coated. Figure 2 As shown, it is assembled into a laminated composite power system.

[0067] Embodiment 6,

[0068] The preparation method in Example 1 is used. In step S6, when laminating, a composite positive electrode sheet, a lithium titanate negative electrode sheet, a composite positive electrode sheet, a lithium titanate negative electrode sheet, and a carbon-based composite electrode sheet are laminated in sequence. Figure 3 As shown, it is assembled into a laminated composite power system.

[0069] Comparative Example 1

[0070] Compared with Example 1, in Comparative Example 1, the conductive rubber matrix is ​​not added with mesocrystal anatase titanium dioxide, and the other conditions are the same as those in Example 1.

[0071] Comparative Example 2

[0072] Compared with Example 1, the conductive rubber substrate in Comparative Example 2 is not subjected to roughening treatment, and the other conditions are the same as those in Example 1.

[0073] Comparative Example 3

[0074] Compared with Example 1, the power system in Comparative Example 3 is composed of only a lithium-ion battery part (NCM+LTO), and the other conditions are the same as those in Example 1.

[0075] Comparative Example 4

[0076] Compared with Example 1, the power supply system in Comparative Example 4 is composed only of a supercapacitor part (LTO+GN), and the other conditions are the same as those in Example 1.

[0077] Comparative Example 5

[0078] Compared with Example 1, Comparative Example 5 uses a conventional ion battery and uses a conventional current collector instead of a conductive rubber matrix.

[0079] The battery prepared above was subjected to cycle test. Energy density test: The energy density of different embodiments was measured using a battery test instrument. The relationship between voltage and charge was obtained through charge and discharge cycles, and the specific energy density value was calculated. Power density test: Through constant current discharge test, the current and voltage at different discharge rates were recorded, the power density was calculated, and its performance under instantaneous high power output was evaluated.

[0080] Table 1. Comparison of test results of different groups

[0081]

[0082]

[0083] The specific results are shown in Table 1. Combining Examples 1-4 and Comparative Examples 1-4, it can be seen that by adopting the technical solution proposed in the present invention, the key performances such as energy density, power performance and cycle life of the supercapacitor-lithium ion battery composite power system are improved, and Example 1 has the best technical effect. The improvement in electrochemical performance is mainly attributed to: the highly conductive rubber matrix prepared first has good electrical conductivity, flexibility and lightness, and can achieve close interface contact between any two electrodes, significantly improving the energy density and power performance of supercapacitors and lithium ion batteries. The combined use of supercapacitors and lithium ion batteries effectively improves the power performance of lithium ion batteries, prolongs the cycle life, and achieves simultaneous improvement in energy density and power performance.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-power lithium-ion power battery, characterized in that: It comprises a stacked composite positive electrode sheet, a lithium titanate negative electrode sheet and a carbon-based composite electrode sheet, wherein a polymer solid electrolyte is provided between the composite positive electrode sheet and the lithium titanate negative electrode sheet, and between the lithium titanate negative electrode sheet and the carbon-based composite electrode sheet; At least one of the composite positive electrode plate, the lithium titanate negative electrode plate and the carbon-based composite electrode plate uses a conductive rubber matrix as a current collector, and the conductive rubber matrix includes polydimethylsiloxane (PDMS), a conductive material and mesogenic anatase titanium dioxide.

2. A high-power lithium-ion power battery according to claim 1, characterized in that: The stacked composite positive electrode sheet and lithium titanate negative electrode sheet are used as a first stacking unit, and the stacked composite positive electrode sheet, lithium titanate negative electrode sheet and carbon-based composite electrode sheet are used as a second stacking unit, and a plurality of the first stacking units are stacked alternately and then stacked with the second stacking unit, or only a plurality of the second stacking units are stacked alternately, or a plurality of the second stacking units are stacked and then stacked with the first stacking unit; A polymer solid electrolyte is provided between two adjacent first lamination units, between two adjacent second lamination units, and between the first lamination unit and the second lamination unit.

3. A high-power lithium-ion power battery according to claim 2, characterized in that: The two outer side surfaces of the lithium-ion power battery are both provided with polymer solid electrolytes, and the thickness of the polymer solid electrolyte is 5 μm-20 μm.

4. A high-power lithium-ion power battery according to claim 1, characterized in that: The mass ratio of polydimethylsiloxane PDMS, conductive material and mesogenic anatase titanium dioxide powder in the conductive rubber matrix is ​​5-9: 0.05-0.25: 0.15-0.

45.

5. A high-power lithium-ion power battery according to claim 1, characterized in that: The conductive material includes at least one of single-walled carbon nanotubes (SWCNTS), mesoporous carbon, graphene, carbon black, conductive graphite, Ketjen black, covalent organic framework structures (COFs), and metal organic frameworks (MOFs).

6. A high-power lithium-ion power battery according to claim 1, characterized in that: The carbon-based composite electrode plate comprises a conductive agent, a dispersant, a first binder and mesogenic anatase titanium dioxide, with a mass ratio of 81-93:0.5-1.5:1.5-4.0:2.0-4.

5.

7. A high-power lithium-ion power battery according to claim 6, characterized in that: The conductive agent includes at least one of graphene GN, conductive carbon black, conductive graphite, carbon nanotubes, and Ketjen black.

8. A high-power lithium-ion power battery according to claim 1, characterized in that: The composite positive electrode plate comprises a positive electrode material, a sulfide solid electrolyte, a mesocrystal anatase titanium dioxide, a lithium salt and a positive electrode binder, and the molar ratio is 30-50: 3-8: 1.5-5.0: 0.5-2.5: 0.5-1.

5.

9. A high-power lithium-ion power battery according to claim 1, characterized in that: The thickness of the conductive rubber matrix is ​​3 μm-30 μm.

10. A high-power lithium-ion power battery according to any one of claims 1 to 9, characterized in that: The mesocrystalline anatase titanium dioxide powder is prepared in the following manner: a titanium source is dissolved in a 1 mol / L-3 mol / L hydrochloric acid solution, the volume ratio of the titanium source to the hydrochloric acid solution is 1-3:4-10, the mixture is stirred at 40°C-100°C for 40h-60h, and a white product is obtained by centrifugation. The white product is washed with deionized water to remove residual inorganic ions, and the white product is vacuum dried at 80°C-120°C for 12h-36h, and finally calcined in air at 400°C-500°C for 12h-24h to obtain the mesocrystalline anatase titanium dioxide powder.

Citation Information

Patent Citations

  • Electric aircraft composite energy system optimal configuration method and system and storage medium

    CN116049973A

  • Bipolar capacitor auxiliary battery

    CN116131423A